1986
DOI: 10.1136/jcp.39.6.635
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A concentrations during the course of acute ischaemic heart disease.

Abstract: SUMMARY Serum amyloid A concentrations were determined in serial serum samples of 41 patients with confirmed acute myocardial infarction (10 with acute ischaemia and two with myocarditis). A sharp increase in serum amyloid A concentration was observed early at onset of infarct; it peaked on the third day (up to 2200 fold of normal values) and declined towards normal during the following days, if no complications occurred. Different patterns were observed in patients with acute ischaemia or myocarditis.Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…[16][17][18] We found that SAA has a high sensitivity and NPV at the time of sepsis evaluation, therefore can be used as a sensitive marker for the detection of EOS, not missing genuine cases of EOS when levels of SAA remain low. Compared with CRP, SAA was more sensitive at onset of sepsis, rose earlier and in a sharper manner, had higher levels and returned faster to normal values in infants who recovered, allowing an accurate and quick diagnosis of EOS.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] We found that SAA has a high sensitivity and NPV at the time of sepsis evaluation, therefore can be used as a sensitive marker for the detection of EOS, not missing genuine cases of EOS when levels of SAA remain low. Compared with CRP, SAA was more sensitive at onset of sepsis, rose earlier and in a sharper manner, had higher levels and returned faster to normal values in infants who recovered, allowing an accurate and quick diagnosis of EOS.…”
Section: Discussionmentioning
confidence: 99%
“…The APPs exhibiting the earliest positive change after acute MI are SAA and CRP (Table 1). CRP has a doubling time of about 4-8 h after the onset of pain and continues to increase to levels that may be several hundred-fold higher than baseline levels 2-4 days after MI [42]. Significantly increased SAA levels were detected following MI 12 h after the peak of creatine kinase.…”
Section: Saa Measurements During Inflammatory Conditionsmentioning
confidence: 96%
“…Serum amyloid A protein (SAA) is an acute phase apolipoprotein, with the earliest and highest increase rate of all the acute phase proteins, including CRP.The levels of SAA can increase 100 -1000 fold during the acute phase and return to baseline during convalescence [5,14]. The transcriptional increase is induced by cytokines, primarily IL-1, IL-6 and TNF-α [10] or by direct stimulation of bacterial lipopolysaccharide (LPS) [13].…”
Section: Introductionmentioning
confidence: 99%